VIP and CRF reduce ADAMTS expression and function in osteoarthritis synovial fibroblasts. Issue 4 (28th January 2016) - Pérez‐García, Selene; Carrión, Mar; Gutiérrez‐Cañas, Irene; González‐Álvaro, Isidoro; Gomariz, Rosa P.; Juarranz, Yasmina
Abstract: ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family is known to play an important role in the pathogenesis of osteoarthritis (OA), working on aggrecan degradation or altering the integrity of extracellular matrix (ECM). Thus, the main purpose of our study was to define the role of vasoactive intestinal peptide (VIP) and corticotrophin‐releasing factor (CRF), as immunoregulatory neuropeptides, on ADAMTS production in synovial fibroblasts (SF) from OA patients and healthy donors (HD). OA‐ and HD‐SF were stimulated with pro‐inflammatory mediators and treated with VIP or CRF. Both neuropeptides decreased ADAMTS‐4, ‐5, ‐7 and ‐12 expressions, aggrecanase activity, glycosaminoglycans (GAG), and cartilage oligomeric matrix protein (COMP) degradation after stimulation with fibronectin fragments (Fn‐fs) in OA‐SF. After stimulation with interleukin‐1β, VIP reduced ADAMTS‐4 and ‐5, and both neuropeptides decreased ADAMTS‐7 production and COMP degradation. Moreover, VIP and CRF reduced Runx2 and β‐catenin activation in OA‐SF. Our data suggest that the role of VIP and CRF on ADAMTS expression and cartilage degradation could be related to the OA pathology since scarce effects were produced in HD‐SF. In addition, their effects might be greater when a degradation loop has been established, given that they were higher after stimulation with Fn‐fs. Our results point to novel OA therapies based on the use of neuropeptides, since VIP and CRF are able to stop the first critical step, the loss of cartilage aggrecan and the ECM destabilization during joint degradation.